The vehicle purchase tax as a climate policy instrument. (February 2017) - Fridstrøm, Lasse; Østli, Vegard
Highlights: Vehicle purchase taxes and feebates are powerful climate policy instruments. A low carbon fiscal policy for automobile purchases may help electrify the fleet. Its main cost is the higher price of cars with currently small economies of scale. Main long-term benefits consist in reduced energy consumption and CO2 emissions. Fiscal cash flows are transfers, not costs, and in essence economically irrelevant. Abstract: Since 2007, the Norwegian vehicle purchase tax includes a large CO2 emission component. At the same time, generous tax exemptions and privileges are granted to battery electric vehicles. Continued application of the purchase tax instrument may induce large-scale penetration of electric cars into the passenger car stock, thus halving the fleet's fossil fuel consumption and greenhouse gas emissions within two or three decades. The main tangible cost of this low carbon policy is the extra cost of acquiring novel products with currently small economies of scale. This cost difference will decline over time. The main benefits consist in reduced energy consumption and greenhouse gas emissions. We calculate the gross and net tangible cost of the low carbon policy in a long-term perspective, i.e. towards the 2050 horizon. A crucial cost determinant is the speed at which the manufacturing costs of battery and plug-in hybrid electric vehicles will fall. Under moderately optimistic assumptions about impending economies of scale, net tangible costs by 2050 come out in the range €48 to 278 per tonne CO2, depending on the discount rate and on battery replacement costs.